2005
DOI: 10.1242/jeb.01761
|View full text |Cite
|
Sign up to set email alerts
|

Role of biogenic amines and cHH in the crustacean hyperglycemic stress response

Abstract: In this study, we investigated (using bioassays and ELISA) the variation of cHH (crustacean hyperglycemic hormone) level in the eyestalks and hemolymph of Palaemon elegans (Rathke) (Decapoda, Caridea) following injection of serotonin (5-HT) and dopamine (DA) and correlated cHH profile with the variation in amount and time course of glycemia.5-HT induced in P. elegans a rapid and massive release of cHH from the eyestalk into the hemolymph followed by hyperglycemia. On the contrary, DA did not significantly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 39 publications
3
31
0
1
Order By: Relevance
“…In decapod crustaceans, the maintenance of suitable glucose levels in the hemolymph is essential to support the regular functions of various organs and in responses to environmental stress (Verri et al, 2001;Lorenzon et al, 2005;Dutra et al, 2008). The digestion of glycogenic substrates and absorption of glucose via the hepatopancreas are the main sources of hemolymphatic glucose (Verri et al, 2001;Obi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In decapod crustaceans, the maintenance of suitable glucose levels in the hemolymph is essential to support the regular functions of various organs and in responses to environmental stress (Verri et al, 2001;Lorenzon et al, 2005;Dutra et al, 2008). The digestion of glycogenic substrates and absorption of glucose via the hepatopancreas are the main sources of hemolymphatic glucose (Verri et al, 2001;Obi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More particularly, the biogenic amines serotonin (5-HT) and dopamine (DA) have been involved in fear responses and anxiety in mammals (Bonhomme and Esposito, 1998;Nutt, 2001;Graeff and Zangrossi, 2010;Canteras and Graeff, 2014;Fossat et al, 2014;Zangrossi and Graeff, 2014). In crayfish and other decapods, 5-HT has been shown to control the stress response by raising secretion of crustacean hyperglycemic hormones (CHHs), leading to an increase in blood glucose (Lorenzon et al, 2005;Fossat et al, 2014). DA has been also claimed to have such a role, although conflicting observations have been reported (Sarojini et al, 1995;Zou et al, 2003;Lorenzon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In crayfish and other decapods, 5-HT has been shown to control the stress response by raising secretion of crustacean hyperglycemic hormones (CHHs), leading to an increase in blood glucose (Lorenzon et al, 2005;Fossat et al, 2014). DA has been also claimed to have such a role, although conflicting observations have been reported (Sarojini et al, 1995;Zou et al, 2003;Lorenzon et al, 2005). Downstream from the stress response, 5-HT is able to trigger ALB in crayfish (Fossat et al, 2014), but the possible role of DA on this behavior has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Lorenzon et al (2000) reported that heavy metals, such as Cd, Hg and Cu produced significant hyperglycaemic response in blood glucose levels of P. elegans exposed to sub lethal concentrations of these heavy metals. Cu contamination induced variation of serotonin (5-HT) of the eyestalk and haemolymph of P. elegans (Lorenzon et al 2005). The release of 5-HT from the eyestalk into the haemolymph after Cu exposure precedes in its time course the release of crustacean hyperglycaemic hormone (cHH), confirming its role as neurotransmitter acting on cHH neuroendocrine cells.…”
Section: Discussionmentioning
confidence: 94%